An Overnight Sucess : Vietnam's Switch to Unleaded Gasoline - World Bank (Washington, DC, 2014)
On July 1, 2000 Vietnam took an important environmental step by switching to ULG (Unleaded gasoline) virtually overnight. This report describes the process that lead up to this decision. It also discusses issues that Vietnam encountered as it proceeded to eliminate LG (Leaded gasoline). After a description of the initial attempts to eliminate leaded gasoline (LG) which began with the passage of transport-related environmental regulations in 1995, chapter 1 discusses: the health impacts of lead; lead levels in Vietnam; automobile and motorcycle fleet growth; gasoline consumption and imports; and domestic refining. Chapter 2 describes the initial efforts, technical and financial constrains. Chapter 3 reviews government leadership and consensus building. Chapter 4 relates preparations for implementation; and chapter lessons learned for others countries. The report also contains: technical specifications for ULG; official laws and decrees; and lists a timetable of decisions and events. In switching to ULG, Vietnam has shown environmental leadership and concern for the health of its citizens. The authors commend the Government of Vietnam for its commitment and for the expedience with which the switch was made. By its positive example, Vietnam can help persuade countries which still use LPG (Leaded gasoline) to switch to ULG (Unleaded gasoline) and to remove one of the most serious, and truly avoidable, human threats.